Method for producing silica particle, method for producing silica sol, polishing method, method for manufacturing semiconductor wafer and method for manufacturing semiconductor device
By purifying methanol with ion exchange resins and refining silica particles through hydrolysis and condensation reactions, the method effectively reduces metal impurities, improving the purity and performance of silica particles for semiconductor polishing.
Patent Information
- Application Number
- JP2024171238
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2020-02-03
- Filing Date
- 2024-09-30
- Publication Date
- 2024-12-19
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing methods for producing silica particles through hydrolysis and condensation reactions of alkoxysilanes fail to sufficiently reduce metal impurities, particularly zinc and iron, which can contaminate semiconductor materials during polishing, affecting electrical properties.
A method involving the purification of methanol using ion exchange resins, followed by a hydrolysis and condensation reaction of tetraalkoxysilane, and subsequent steps to refine silica particles, including concentration and pressurized heating, to achieve ultra-high purity.
The method significantly reduces zinc and iron content in silica particles and sols, minimizing contamination during semiconductor polishing and enhancing the quality of polished surfaces.
Smart Images

Figure 2024177258000001 
Figure 2024177258000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing silica particles, a method for producing a silica sol, a polishing method, a method for producing a semiconductor wafer, and a semiconductor device. [Background technology]
[0002] Polishing methods using polishing liquids are known as methods for polishing the surfaces of materials such as metals and inorganic compounds. In particular, in the final polishing of prime silicon wafers for semiconductors and reclaimed silicon wafers, and in chemical mechanical polishing (CMP) for planarizing interlayer insulating films during semiconductor device manufacturing, forming metal plugs, forming buried wiring, and the like, the surface condition has a significant effect on the semiconductor characteristics, so the surfaces and end faces of these components are required to be polished with extremely high precision.
[0003] In such precision polishing, a polishing composition containing silica particles is adopted, and colloidal silica is widely used as the abrasive grains, which are the main component. Depending on the manufacturing method, colloidal silica is known to be produced by pyrolysis of silicon tetrachloride (fumed silica, etc.), by deionization of alkali silicate such as water glass, and by hydrolysis and condensation reaction of alkoxysilane (generally called the "sol-gel method").
[0004] Many studies have been conducted on methods for producing colloidal silica. For example, Patent Documents 1 to 3 disclose methods for producing silica sol by hydrolysis and condensation reactions of alkoxysilane. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Japanese Patent Application Publication No. 11-60232 [Patent Document 2] JP 2005-060217 A [Patent Document 3] JP 2018-108924 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, the silica particles obtained by the hydrolysis and condensation reactions of alkoxysilanes do not have a sufficiently low metal content. In general, when silica particles are produced by the hydrolysis and condensation reactions of alkoxysilanes, alcohols such as methanol are often used as a solvent or reaction liquid for alkoxysilanes. The metals contained in this methanol are not distilled off together with the solvent and remain in the silica particles. Among metals, zinc is used as a catalyst when producing methanol, so it is contained in large amounts as an impurity in methanol. In addition, iron is generally eluted from stainless steel cans and piping used to store and transport methanol, so it is contained in large amounts as an impurity in methanol. Therefore, zinc and iron tend to remain in the dispersion of silica particles. If the dispersion of silica particles contains a large amount of metals such as zinc and iron, there is a problem that when polishing semiconductor materials such as silicon wafers, the metals adhere to the surface and have a negative effect on the electrical properties.
[0007] The methods for producing silica particles by hydrolysis and condensation reactions of alkoxysilanes disclosed in Patent Documents 1 to 3 do not involve any treatment to reduce the metals in the methanol used, and therefore the metal content in the resulting dispersion of silica particles cannot be said to be sufficiently low.
[0008] The present invention has been made in consideration of such problems, and an object of the present invention is to provide a method for producing silica particles that can reduce the content of metals, particularly zinc and iron. [Means for solving the problem]
[0009] The conventional method of producing silica particles by hydrolysis and condensation of alkoxysilane cannot sufficiently reduce the metals, especially zinc and iron, in the methanol used for production, and it is difficult to obtain ultra-high purity silica particles.The present inventors have conducted extensive research and found that by purifying methanol with ion exchange resin and using the purified methanol for producing silica particles, ultra-high purity silica particles can be obtained, and have completed the present invention.
[0010] That is, the gist of the present invention is as follows. [1] A method for producing silica particles, comprising the following steps (1) and (2): Step (1): Purifying methanol using an ion exchange resin Step (2): A step of adding a solution (B) containing tetraalkoxysilane to a solution (A) containing methanol purified in step (1) to cause a hydrolysis reaction and a condensation reaction of the tetraalkoxysilane. [2] The method for producing silica particles according to [1], wherein the ion exchange resin in step (1) includes a cation exchange resin and an anion exchange resin. [3] The method for producing silica particles according to [2], wherein the cation exchange resin includes a strongly acidic cation exchange resin. [4] The method for producing silica particles according to [2] or [3], wherein the anion exchange resin comprises a strongly basic anion exchange resin. [5] The method for producing silica particles according to any one of [1] to [4], wherein the solution (B) contains methanol purified in the step (1). [6] The method for producing silica particles according to any one of [1] to [5], further comprising the following step (3): Step (3): A step of concentrating the dispersion of silica particles obtained in step (2) and replacing the dispersion medium. [7] The method for producing silica particles according to [6], further comprising the following step (4): Step (4): A step of subjecting the dispersion of silica particles obtained in step (3) to a pressurized and heated treatment. [8] A method for producing a silica sol, comprising the method for producing silica particles according to any one of [1] to [7]. [9] The method for producing a silica sol according to [8], wherein the content of silica particles in the silica sol is 10% by mass to 25% by mass.
[10] The method for producing a silica sol according to [8] or [9], wherein the zinc content in the silica sol is 50 ppb or less.
[11] The method for producing a silica sol according to any one of [8] to
[10] , wherein the iron content in the silica sol is 4 ppb or less.
[12] A polishing method, comprising the steps of: polishing with a polishing composition containing silica particles obtained by the method for producing silica particles according to any one of [1] to [7].
[13] A method for producing a semiconductor wafer, comprising the polishing method according to
[12] .
[14] A method for manufacturing a semiconductor device, comprising the polishing method according to
[12] . Effect of the Invention
[0011] The method for producing silica particles of the present invention can reduce the metal content, particularly zinc and iron, of the resulting silica particles. Also, the method for producing silica sol of the present invention can reduce the metal content, particularly zinc and iron, of the resulting silica sol. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The present invention will be described in detail below, but the present invention is not limited to the following embodiments and can be modified and practiced in various ways within the scope of the gist. In addition, when the expression "~" is used in this specification, it is used as an expression including the numerical values or physical property values before and after it.
[0013] The method for producing silica particles of the present invention includes the following steps (1) and (2). Step (1): Purifying methanol using an ion exchange resin Step (2): A step of adding a solution (B) containing tetraalkoxysilane to a solution (A) containing methanol purified in step (1) to cause a hydrolysis reaction and a condensation reaction of the tetraalkoxysilane.
[0014] (Process (1)) Step (1) is a step of purifying methanol with an ion exchange resin.
[0015] As the methanol, a commercially available product may be used, and examples thereof include methanol manufactured by Kanto Chemical Co., Ltd., methanol manufactured by Sumitomo Chemical Co., Ltd., methanol manufactured by Kishida Chemical Co., Ltd., methanol manufactured by Takasugi Pharmaceutical Co., Ltd., and methanol manufactured by Mitsubishi Chemical Corporation.
[0016] An ion exchange resin is a synthetic resin having a chemical structure into which functional groups having ion exchange capacity have been introduced.
[0017] It is preferable to use a cation exchange resin since it has excellent ability to remove metals present in methanol as cations, and it is more preferable to use a combination of a cation exchange resin and an anion exchange resin since it can suppress fluctuations in the pH of methanol during the purification process.
[0018] Examples of the cation exchange resin include strong acid cation exchange resins such as "Diaion (trade name)" SK series and "Diaion (trade name)" PK series manufactured by Mitsubishi Chemical Corporation; weak acid cation exchange resins such as "Diaion (trade name)" WK series manufactured by Mitsubishi Chemical Corporation and "Diaion (trade name)" WK40L manufactured by Mitsubishi Chemical Corporation. These cation exchange resins may be used alone or in combination of two or more kinds. Among these cation exchange resins, strong acid cation exchange resins are preferred because they have excellent cation exchange capacity even for neutral salts.
[0019] Examples of the ion exchange group of the cation exchange resin include a sulfonic acid group and a carboxylic acid group. The ion exchange group of these cation exchange resins may be used alone or in combination of two or more. Among the ion exchange groups of these cation exchange resins, the sulfonic acid group is preferred because it has excellent cation exchange capacity for neutral salts.
[0020] Examples of the anion exchange resin include strongly basic anion exchange resins such as "Diaion (trade name)" SA series manufactured by Mitsubishi Chemical Corporation; and weakly basic anion exchange resins such as "Diaion (trade name)" WA10 manufactured by Mitsubishi Chemical Corporation and "Diaion (trade name)" WA20 manufactured by Mitsubishi Chemical Corporation. These anion exchange resins may be used alone or in combination of two or more kinds. Among these anion exchange resins, strongly basic anion exchange resins are preferred because they have excellent anion exchange capacity even for neutral salts.
[0021] Examples of the ion exchange groups of the anion exchange resin include trimethylammonium groups, dimethylethanolammonium groups, polyamine groups, and tertiary amino groups. The ion exchange groups of these anion exchange resins may be used alone or in combination of two or more. Among the ion exchange groups of these anion exchange resins, the trimethylammonium group is preferred because it has excellent anion exchange capacity for neutral salts.
[0022] Examples of the ion exchange resin material include styrene-based resins, acrylic-based resins, etc. Among these ion exchange resin materials, styrene-based resins and acrylic-based resins are preferred, and styrene-based resins are more preferred, since functional groups having ion exchange ability can be easily introduced therein and they have excellent purification ability.
[0023] Examples of the form of the ion exchange resin include a gel type, a porous type, etc. Among these forms of the ion exchange resin, the gel type is preferred because it has excellent efficiency in purifying methanol.
[0024] The method of purifying methanol with an ion exchange resin is not particularly limited, and examples thereof include a method of passing methanol through a vessel filled with an ion exchange resin, a method of placing an ion exchange resin and methanol in a vessel and contacting them, and then filtering out the ion exchange resin to recover methanol, etc. Among these purification methods, the method of passing methanol through a vessel filled with an ion exchange resin is preferred because it has excellent purification efficiency for methanol.
[0025] (Process (2)) Step (2) is a step of adding a solution (B) containing a tetraalkoxysilane to a solution (A) containing the methanol purified in step (1) to cause a hydrolysis reaction and a condensation reaction of the tetraalkoxysilane.
[0026] Solution (A) contains the methanol purified in step (1).
[0027] The solution (A) preferably contains water in addition to the methanol purified in step (1) because this promotes the hydrolysis and condensation reaction of the tetraalkoxysilane.
[0028] In addition to the methanol purified in step (1), the solution (A) preferably contains an alkali catalyst, since this can increase the reaction rates of the hydrolysis reaction and condensation reaction of the tetraalkoxysilane.
[0029] Examples of the alkali catalyst in the solution (A) include ethylenediamine, diethylenetriamine, triethylenetetraamine, ammonia, urea, ethanolamine, and tetramethylammonium hydroxide. These alkali catalysts may be used alone or in combination of two or more. Among these alkali catalysts, ammonia is preferred because it has excellent catalytic action, can suppress metal contamination, is highly volatile, and is easy to remove after hydrolysis and condensation reactions.
[0030] The solution (B) contains a tetraalkoxysilane.
[0031] Examples of the tetraalkoxysilane in the solution (B) include tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, and tetraisopropoxysilane. These tetraalkoxysilanes may be used alone or in combination of two or more. Among these tetraalkoxysilanes, tetramethoxysilane and tetraethoxysilane are preferred, and tetramethoxysilane is more preferred, because they undergo a fast hydrolysis reaction, are less likely to leave unreacted substances, are highly productive, and can easily produce a stable silica sol.
[0032] The raw materials for the silica particles may be raw materials other than tetraalkoxysilane, such as low condensates of tetraalkoxysilane. However, due to their excellent reactivity, it is preferable that, out of 100 mass% of all raw materials constituting the silica particles, tetraalkoxysilane accounts for 50 mass% or more and raw materials other than tetraalkoxysilane accounts for 50 mass% or less, and it is more preferable that tetraalkoxysilane accounts for 90 mass% or more and raw materials other than tetraalkoxysilane accounts for 10 mass% or less.
[0033] The solution (B) may contain only tetraalkoxysilane without containing a solvent, but it is preferable that the solution (B) contains a solvent, since this improves the dispersibility of the tetraalkoxysilane in the reaction liquid.
[0034] Examples of the solvent in the solution (B) include methanol, ethanol, propanol, isopropanol, and ethylene glycol. These solvents may be used alone or in combination of two or more. Among these solvents, alcohol is preferred because the by-products produced in the hydrolysis reaction and condensation reaction are the same as those used in the hydrolysis reaction and condensation reaction, and are therefore convenient to manufacture. Methanol is more preferred, and methanol purified in step (1) is even more preferred because it can reduce the metal content of the silica particles.
[0035] It is preferable to add a solution (C) containing an alkali catalyst to the solution (A) in addition to the solution (B) containing a tetraalkoxysilane, since this can increase the reaction rates of the hydrolysis reaction and condensation reaction of the tetraalkoxysilane.
[0036] Examples of the alkali catalyst in the solution (C) include ethylenediamine, diethylenetriamine, triethylenetetraamine, ammonia, urea, ethanolamine, and tetramethylammonium hydroxide. These alkali catalysts may be used alone or in combination of two or more. Among these alkali catalysts, ammonia is preferred because it has excellent catalytic action, is easy to control the particle shape, can suppress metal contamination, is highly volatile, and is easy to remove after hydrolysis and condensation reactions.
[0037] It is preferable that the solution (C) contains a solvent, since this can reduce fluctuations in the concentration of the alkali catalyst in the reaction liquid.
[0038] Examples of the solvent in the solution (C) include water, methanol, ethanol, propanol, isopropanol, and ethylene glycol. These solvents may be used alone or in combination of two or more. Among these solvents, water and alcohol are preferred, and water is more preferred, because the solvents used in the hydrolysis reaction and the condensation reaction are the same as the by-products, and are convenient in production.
[0039] Since the method for producing silica particles of the present invention can remove unnecessary components and add necessary components, it is preferable that the method further includes the following step (3). Step (3): A step of concentrating the dispersion of silica particles obtained in step (2) and adding a dispersion medium.
[0040] Examples of the dispersion medium include water, methanol, ethanol, propanol, isopropanol, and ethylene glycol. These dispersion media may be used alone or in combination of two or more. Among these dispersion media, water and alcohol are preferred, and water is more preferred, because they have excellent affinity with silica particles.
[0041] The method for producing silica particles of the present invention preferably further includes the following step (4) since the condensation degree of the silica particles can be increased. Step (4): A step of subjecting the dispersion of silica particles obtained in step (3) to a pressurized and heated treatment.
[0042] The pressure of the pressurized heat treatment is preferably 0.10 MPa to 2.3 MPa, more preferably 0.14 MPa to 1.0 MPa. When the pressure of the pressurized heat treatment is 0.10 MPa or more, the degree of condensation of the silica particles can be increased. When the pressure of the pressurized heat treatment is 2.3 MPa or less, the silica particles can be produced without significant changes in the average primary particle size, average secondary particle size, and association ratio, and the dispersion stability of the silica sol is excellent. Pressurization can be achieved by heating the silica particle dispersion in a sealed state to above the boiling point of the dispersion medium. When the silica particle aqueous dispersion is heated to 100°C or higher in a sealed state, the pressure becomes the saturated water vapor pressure at that temperature.
[0043] The temperature of the pressure and heat treatment is preferably 100° C. to 220° C., and more preferably 110° C. to 180° C. When the temperature of the pressure and heat treatment is 100° C. or higher, the degree of condensation of the silica particles can be increased. When the temperature of the pressure and heat treatment is 220° C. or lower, silica particles can be produced without significant changes in the average primary particle size, average secondary particle size, and association ratio, and the dispersion stability of the silica sol is excellent.
[0044] The time of the pressurized heat treatment is preferably 0.25 hours to 10 hours, and more preferably 0.5 hours to 8 hours. When the time of the pressurized heat treatment is 0.25 hours or more, the degree of condensation of the silica particles can be increased. When the time of the pressurized heat treatment is 10 hours or less, the silica particles can be produced without significant changes in the average primary particle size, the average secondary particle size, and the association ratio, and the dispersion stability of the silica sol is excellent.
[0045] The pressurized heat treatment is preferably carried out in an aqueous dispersion because it can increase the degree of condensation of the silica particles without significantly changing the average primary particle size, the average secondary particle size, and the association ratio.
[0046] The pH when the pressure heat treatment is carried out in the aqueous dispersion is preferably 6.0 to 8.0, more preferably 6.5 to 7.8. When the pH when the pressure heat treatment is carried out in the aqueous dispersion is 6.0 or more, gelation of the silica sol can be suppressed. When the pH when the pressure heat treatment is carried out in the aqueous dispersion is 8.0 or less, the degree of condensation of the silica particles can be increased without significantly changing the average primary particle size, the average secondary particle size, and the association ratio.
[0047] The average primary particle diameter of the silica particles is preferably 5 nm to 100 nm, more preferably 10 nm to 60 nm. When the average primary particle diameter of the silica particles is 5 nm or more, the storage stability of the silica sol is excellent. Furthermore, when the average primary particle diameter of the silica particles is 100 nm or less, the surface roughness and scratches of the polished object, such as a silicon wafer, can be reduced, and the sedimentation of the silica particles can be suppressed.
[0048] The average primary particle size of the silica particles is measured by the BET method. Specifically, the specific surface area of the silica particles is measured using an automatic specific surface area measuring device, and the average primary particle size is calculated using the following formula (1). Average primary particle diameter (nm) = 6000 / (specific surface area (m 2 / g) x density (g / cm 3 )) ··· (1)
[0049] The average primary particle size of the silica particles can be set within a desired range by known conditions and methods.
[0050] The average secondary particle diameter of the silica particles is preferably 10 nm to 200 nm, more preferably 20 nm to 100 nm. When the average secondary particle diameter of the silica particles is 10 nm or more, the removability of particles and the like during cleaning after polishing is excellent, and the storage stability of the silica sol is excellent. When the average secondary particle diameter of the silica particles is 200 nm or less, the surface roughness and scratches of the polished object, typically a silicon wafer, during polishing can be reduced, and the removability of particles and the like during cleaning after polishing can be excellent, and sedimentation of the silica particles can be suppressed.
[0051] The average secondary particle size of the silica particles is measured by a DLS method, specifically, using a dynamic light scattering particle size measuring device.
[0052] The average secondary particle size of the silica particles can be set within a desired range by known conditions and methods.
[0053] The cv value of the silica particles is preferably 15 to 50, more preferably 20 to 40, and even more preferably 25 to 35. When the cv value of the silica particles is 15 or more, the polishing rate for a polished object such as a silicon wafer is excellent, and the productivity of the silicon wafer is excellent. When the cv value of the silica particles is 50 or less, the surface roughness and scratches of a polished object such as a silicon wafer during polishing can be reduced, and the removability of particles and the like during cleaning after polishing is excellent.
[0054] The cv value of the silica particles is calculated using the following formula (2) by measuring the average secondary particle size of the silica particles using a dynamic light scattering particle size measuring device. cv value = (standard deviation (nm) / average secondary particle size (nm)) × 100 (2)
[0055] The association ratio of the silica particles is preferably 1.0 to 4.0, more preferably 1.1 to 3.0. When the association ratio of the silica particles is 1.0 or more, the polishing rate for the polished object, typically a silicon wafer, is excellent, and the productivity of the silicon wafer is excellent. When the association ratio of the silica particles is 4.0 or less, the surface roughness and scratches of the polished object, typically a silicon wafer, during polishing can be reduced, and the aggregation of the silica particles can be suppressed.
[0056] The association ratio of the silica particles is calculated using the following formula (3) from the average primary particle diameter measured by the above-mentioned measurement method and the average secondary particle diameter measured by the above-mentioned measurement method. Association ratio = average secondary particle diameter / average primary particle diameter (3)
[0057] Examples of the shape of silica particles include spherical, chain-like, cocoon-like (also called lump-like or peanut-like), irregular shapes (for example, wart-like, bent, branched, etc.) etc. Among these silica particle shapes, when it is desired to reduce the surface roughness or scratches of a polished object, such as a silicon wafer, during polishing, a spherical shape is preferred, and when it is desired to increase the polishing rate of a polished object, such as a silicon wafer, an irregular shape is preferred.
[0058] Silica particles preferably have no pores because they have excellent mechanical strength and storage stability. The presence or absence of pores in the silica particles is confirmed by multipoint BET analysis using adsorption isotherms with nitrogen as the adsorption gas.
[0059] (Method of producing silica sol) The method for producing a silica sol of the present invention includes the method for producing silica particles of the present invention.
[0060] The silica sol may be produced by using the dispersion liquid of silica particles obtained by the method for producing silica particles of the present invention as is, or by removing unnecessary components from the components in the reaction liquid obtained in step (2) and adding necessary components.
[0061] The production of the silica sol may include a filtration step in order to remove coarse particles and to avoid aggregation of fine particles. Examples of the filtration method include natural filtration under normal pressure, reduced pressure filtration, pressure filtration, centrifugal filtration, and the like. Filtration may be carried out at any timing and any number of times, but is preferably carried out immediately before preparation of the polishing composition, as this results in excellent storage stability and polishing properties of the polishing composition.
[0062] The silica sol preferably contains silica particles and a dispersion medium. Examples of the dispersion medium of silica sol include water, methanol, ethanol, propanol, isopropanol, ethylene glycol, etc. These dispersion mediums of silica sol may be used alone or in combination of two or more. Among these dispersion mediums of silica sol, water and alcohol are preferred, and water is more preferred, because they have excellent affinity with silica particles.
[0063] The content of silica particles in the silica sol is preferably 3% by mass to 50% by mass, more preferably 4% by mass to 40% by mass, and even more preferably 5% by mass to 30% by mass, based on the total amount of the silica sol (100% by mass). When the content of silica particles in the silica sol is 3% by mass or more, the polishing rate for a polished object such as a silicon wafer is excellent. When the content of silica particles in the silica sol is 50% by mass or less, the aggregation of silica particles in the silica sol or polishing composition can be suppressed, and the storage stability of the silica sol or polishing composition is excellent.
[0064] The content of the dispersion medium in the silica sol is preferably 50% by mass to 97% by mass, more preferably 60% by mass to 96% by mass, and even more preferably 70% by mass to 95% by mass, based on the total amount of the silica sol (100% by mass). When the content of the dispersion medium in the silica sol is 50% by mass or more, the aggregation of silica particles in the silica sol or polishing composition can be suppressed, and the storage stability of the silica sol or polishing composition is excellent. In addition, when the content of the dispersion medium in the silica sol is 97% by mass or less, the polishing rate for the polished object, typically a silicon wafer, is excellent.
[0065] The content of silica particles and dispersion medium in the silica sol can be set within the desired range by removing unnecessary components from the dispersion of silica particles obtained by the silica particle manufacturing method of the present invention and adding necessary components.
[0066] In addition to the silica particles and the dispersion medium, the silica sol may contain other components such as an oxidizing agent, a preservative, an antifungal agent, a pH adjuster, a pH buffer, a surfactant, a chelating agent, and an antibacterial and biocide, as necessary, within the range that does not impair the performance of the silica sol. In particular, it is preferable to include an antibacterial biocide in the silica sol, since this provides excellent storage stability of the silica sol.
[0067] Examples of antibacterial biocides include hydrogen peroxide, ammonia, quaternary ammonium hydroxide, quaternary ammonium salt, ethylenediamine, glutaraldehyde, hydrogen peroxide, methyl p-hydroxybenzoate, sodium chlorite, etc. These antibacterial biocides may be used alone or in combination of two or more. Among these antibacterial biocides, hydrogen peroxide is preferred because it has excellent affinity with silica sol. Biocides also include those commonly referred to as bactericides.
[0068] The content of the antibacterial biocide in the silica sol is preferably 0.0001% by mass to 10% by mass, more preferably 0.001% by mass to 1% by mass, based on the total amount of the silica sol (100% by mass). When the content of the antibacterial biocide in the silica sol is 0.0001% by mass or more, the storage stability of the silica sol is excellent. When the content of the antibacterial biocide in the silica sol is 10% by mass or less, the inherent performance of the silica sol is not impaired.
[0069] The pH of the silica sol is preferably 6.0 to 8.0, more preferably 6.5 to 7.8. When the pH of the silica sol is 6.0 or more, the dispersion stability is excellent and the aggregation of the silica particles can be suppressed. Also, when the pH of the silica sol is 8.0 or less, dissolution of the silica particles is prevented and the long-term storage stability is excellent. The pH of the silica sol can be adjusted to a desired range by adding a pH adjuster.
[0070] When polishing silicon wafers for semiconductor devices, metals adhere to and contaminate the surface of the workpiece to be polished, adversely affecting the characteristics of the silicon wafer and diffusing into the interior of the wafer, degrading its quality, resulting in a significant decrease in the performance of semiconductor devices manufactured from such silicon wafers. Furthermore, when a metal is present in the silica sol, a coordination interaction occurs between the acidic surface silanol groups and the metal, changing the chemical properties (acidity, etc.) of the surface silanol groups and the three-dimensional environment of the silica particle surface (e.g. the ease of aggregation of silica particles), thereby affecting the polishing rate.
[0071] The zinc content in the silica sol is preferably 50 ppb or less, more preferably 30 ppb or less. When the zinc content in the silica sol is 50 ppb or less, contamination of the silicon wafer surface can be reduced when the silicon wafer is polished.
[0072] The iron content in the silica sol is preferably 4 ppb or less, more preferably 3 ppb or less. When the iron content in the silica sol is 4 ppb or less, contamination of the silicon wafer surface can be reduced when the silicon wafer is polished.
[0073] The zinc and iron content in silica sol is measured by inductively coupled plasma mass spectrometry (ICP-MS). Specifically, 0.5 g of silica sol is accurately weighed, sulfuric acid and hydrofluoric acid are added, and the mixture is heated, dissolved, and evaporated. Pure water is added to the remaining droplets to create a test solution, which is then measured using an inductively coupled plasma mass spectrometry device.
[0074] (polishing composition) The silica particles obtained by the method for producing silica particles of the present invention can be suitably used as a polishing composition. The polishing composition preferably contains the above-mentioned silica sol and a water-soluble polymer.
[0075] The water-soluble polymer enhances the wettability of the polishing composition to the object to be polished, such as a silicon wafer. The water-soluble polymer is preferably a polymer having a functional group with high water affinity, and the functional group with high water affinity has a high affinity with the surface silanol group of the silica particles, so that the silica particles and the water-soluble polymer are stably dispersed in the polishing composition in a closer vicinity. Therefore, when polishing the object to be polished, such as a silicon wafer, the effects of the silica particles and the water-soluble polymer function synergistically.
[0076] Examples of the water-soluble polymer include cellulose derivatives, polyvinyl alcohol, polyvinylpyrrolidone, copolymers having a polyvinylpyrrolidone skeleton, and polymers having a polyoxyalkylene structure.
[0077] Examples of cellulose derivatives include hydroxyethyl cellulose, hydrolyzed hydroxyethyl cellulose, hydroxypropyl cellulose, hydroxyethyl methyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose, ethyl cellulose, ethyl hydroxyethyl cellulose, and carboxymethyl cellulose. An example of the copolymer having a polyvinylpyrrolidone skeleton is a graft copolymer of polyvinyl alcohol and polyvinylpyrrolidone. Examples of polymers having a polyoxyalkylene structure include polyoxyethylene, polyoxypropylene, and copolymers of ethylene oxide and propylene oxide.
[0078] These water-soluble polymers may be used alone or in combination of two or more. Among these water-soluble polymers, cellulose derivatives are preferred, and hydroxyethyl cellulose is more preferred, because they have high affinity with the surface silanol groups of silica particles and act synergistically to impart good hydrophilicity to the surface of the polished object.
[0079] The mass average molecular weight of the water-soluble polymer is preferably 1,000 to 3,000,000, more preferably 5,000 to 2,000,000, and even more preferably 10,000 to 1,000,000. When the mass average molecular weight of the water-soluble polymer is 1,000 or more, the hydrophilicity of the polishing composition is improved. When the mass average molecular weight of the water-soluble polymer is 3,000,000 or less, the affinity with silica sol is excellent, and the polishing rate for the object to be polished, typified by a silicon wafer, is excellent.
[0080] The mass average molecular weight of the water-soluble polymer is measured by size exclusion chromatography using a 0.1 mol / L NaCl solution as the mobile phase, in terms of polyethylene oxide.
[0081] The content of the water-soluble polymer in the polishing composition is preferably 0.02% by mass to 10% by mass, more preferably 0.05% by mass to 5% by mass, based on the total amount of the polishing composition (100% by mass). When the content of the water-soluble polymer in the polishing composition is 0.02% by mass or more, the hydrophilicity of the polishing composition is improved. Furthermore, when the content of the water-soluble polymer in the polishing composition is 10% by mass or less, the aggregation of silica particles during preparation of the polishing composition can be suppressed.
[0082] In addition to the silica sol and the water-soluble polymer, the polishing composition may contain other components, such as a basic compound, a polishing accelerator, a surfactant, a hydrophilic compound, a preservative, an antifungal agent, a pH adjuster, a pH buffer, a surfactant, a chelating agent, an antibacterial agent or a biocide, as necessary, within the range that does not impair the performance of the polishing composition. In particular, it is preferable to include a basic compound in the polishing composition, since it is possible to perform chemical polishing (chemical etching) by applying a chemical action to the surface of an object to be polished, such as a silicon wafer, and because a synergistic effect with the surface silanol groups of the silica particles can improve the polishing speed of an object to be polished, such as a silicon wafer.
[0083] Examples of the basic compound include organic basic compounds, alkali metal hydroxides, alkali metal hydrogen carbonates, alkali metal carbonates, and ammonia. These basic compounds may be used alone or in combination of two or more. Among these basic compounds, ammonia, tetramethylammonium hydroxide, tetraethylammonium hydroxide, ammonium hydrogen carbonate, and ammonium carbonate are preferred because they are highly soluble in water and have excellent affinity with silica particles and water-soluble polymers, and ammonia, tetramethylammonium hydroxide, and tetraethylammonium hydroxide are more preferred, with ammonia being even more preferred.
[0084] The content of the basic compound in the polishing composition is preferably 0.001% by mass to 5% by mass, more preferably 0.01% by mass to 3% by mass, based on the total amount of the polishing composition (100% by mass). When the content of the basic compound in the polishing composition is 0.001% by mass or more, the polishing speed of the object to be polished, such as a silicon wafer, can be improved. In addition, when the content of the basic compound in the polishing composition is 5% by mass or less, the stability of the polishing composition is excellent.
[0085] The pH of the polishing composition is preferably 8.0 to 12.0, more preferably 9.0 to 11.0. When the pH of the polishing composition is 8.0 or more, the aggregation of silica particles in the polishing composition can be suppressed, and the dispersion stability of the polishing composition is excellent. When the pH of the polishing composition is 12.0 or less, the dissolution of silica particles can be suppressed, and the stability of the polishing composition is excellent. The pH of the polishing composition can be adjusted to a desired range by adding a pH adjuster.
[0086] The polishing composition can be obtained by mixing the silica sol of the present invention, the water-soluble polymer, and, if necessary, other components. However, taking into consideration storage and transportation, the composition may be prepared at a high concentration and then diluted with water or the like immediately before polishing.
[0087] (polishing method) The polishing method of the present invention is a polishing method using a polishing composition containing silica particles obtained by the method for producing silica particles of the present invention. As the polishing composition, it is preferable to use the above-mentioned polishing composition. A specific example of the polishing method is a method in which the surface of a silicon wafer is pressed against a polishing pad, the polishing composition of the present invention is dropped onto the polishing pad, and the surface of the silicon wafer is polished.
[0088] (Application) The silica particles obtained by the method for producing silica particles of the present invention and the silica sol obtained by the method for producing a silica sol of the present invention can be suitably used for polishing purposes, for example, polishing semiconductor materials such as silicon wafers, polishing electronic materials such as hard disk substrates, polishing (chemical mechanical polishing) in the planarization process when producing integrated circuits, polishing synthetic quartz glass substrates used for photomasks and liquid crystals, polishing magnetic disk substrates, and the like, and among these, they can be particularly suitably used for polishing silicon wafers and chemical mechanical polishing. EXAMPLES
[0089] The present invention will be described in more detail below using examples. However, the present invention is not limited to the description of the following examples as long as it does not deviate from the gist of the present invention.
[0090] (Measurement of average primary particle size) The silica sol obtained in the examples and comparative examples was dried at 150°C, and the specific surface area of the silica particles was measured using an automatic specific surface area measuring device "BELSORP-MR1" (model name, Microtrack BEL Co., Ltd.). The density was calculated to be 2.2 g / cm using the following formula (1). 3 The average primary particle size was calculated. Average primary particle diameter (nm) = 6000 / (specific surface area (m 2 / g) x density (g / cm 3 )) ··· (1)
[0091] (Measurement of average secondary particle size and cv value) The average secondary particle size of the silica particles in the silica sols obtained in the examples and comparative examples was measured using a dynamic light scattering particle size measurement device "Zetersizer Nano ZS" (model name, manufactured by Malvern Instruments), and the cv value was calculated using the following formula (2). cv value = (standard deviation (nm) / average secondary particle size (nm)) × 100 (2)
[0092] (Calculation of association ratio) The association ratio was calculated from the measured average primary particle size and average secondary particle size using the following formula (3). Association ratio = average secondary particle diameter / average primary particle diameter (3)
[0093] (Measurement of zinc and iron content in methanol) 10 g of methanol obtained in the reference example was accurately weighed out and evaporated to dryness on a hot plate. Nitric acid was added to the solid remaining on the hot plate and dissolved by heating, and the remaining droplets were collected and the volume was adjusted to prepare a test solution, and the zinc and iron contents were measured using a high-frequency inductively coupled plasma mass spectrometer "ELEMENT2" (model name, manufactured by Thermo Fisher Scientific).
[0094] (Measurement of zinc and iron content in silica sol) 0.5 g of the silica sol obtained in each of the examples and comparative examples was accurately weighed out, sulfuric acid and hydrofluoric acid were added, and the mixture was heated, dissolved, and evaporated. Pure water was added to the remaining droplets to prepare a test solution, and the zinc and iron contents were measured using a high-frequency inductively coupled plasma mass spectrometer "ELEMENT2" (model name, manufactured by Thermo Fisher Scientific).
[0095] [Comparative Example 1] Methanol manufactured by Kishida Chemical Co., Ltd. was used as is.
[0096] [Comparative Reference Example 2] Methanol manufactured by Mitsubishi Chemical Corporation was used as is.
[0097] [Reference example 1] A tetrafluoroethylene resin tube having an inner diameter of 10 mm and a length of 400 mm was filled with an ion exchange resin ("Diaion (trade name)" SMT200L, manufactured by Mitsubishi Chemical Corporation, including a gel-type styrene-based strongly acidic cation exchange resin in which the ion exchange group is a sulfonic acid group and a gel-type styrene-based strongly basic anion exchange resin in which the ion exchange group is a trimethylammonium group). Methanol of Comparative Reference Example 2 was poured into one end of the tetrafluoroethylene resin tube and passed through the ion exchange resin layer to purify the methanol. The height of the ion-exchange resin layer when the ion-exchange resin was packed in the tetrafluoroethylene resin tube was 175 mm, and the rate at which methanol was poured in was 38 mL / min.
[0098] [Reference example 2] Methanol was purified in the same manner as in Reference Example 1, except that the ion exchange resin was "Diaion (trade name)" SMT100L (manufactured by Mitsubishi Chemical Corporation, including a gel-type styrene-based strongly acidic cation exchange resin in which the ion exchange group is a sulfonic acid group and a gel-type styrene-based strongly basic anion exchange resin in which the ion exchange group is a trimethylammonium group).
[0099] [Reference example 3] Methanol was purified in the same manner as in Reference Example 1, except that the ion exchange resin was changed to "Diaion (product name)" SKT20L (manufactured by Mitsubishi Chemical Corporation, a gel-type styrene-based strongly acidic cation exchange resin in which the ion exchange group is a sulfonic acid group).
[0100] [Reference example 4] Methanol was purified in the same manner as in Reference Example 1, except that the ion exchange resin was changed to "Diaion (product name)" SAT20L (manufactured by Mitsubishi Chemical Corporation, a gel-type styrene-based strongly basic anion exchange resin in which the ion exchange group is a trimethylammonium group).
[0101] [Reference example 5] Methanol was purified in the same manner as in Reference Example 1, except that the ion exchange resin was changed to "Diaion (product name)" WK100 (manufactured by Mitsubishi Chemical Corporation, a porous acrylic weakly acidic cation exchange resin in which the ion exchange group is a carboxylic acid group).
[0102] [Reference example 6] Methanol was purified in the same manner as in Reference Example 1, except that the ion exchange resin was changed to "Diaion (product name)" WA20 (manufactured by Mitsubishi Chemical Corporation, a porous styrene-based weakly basic anion exchange resin in which the ion exchange group is a polyamine group).
[0103] [Reference example 7] Methanol was purified in the same manner as in Reference Example 1, except that the ion exchange resin was changed to "Diaion (product name)" WA30 (manufactured by Mitsubishi Chemical Corporation, a porous styrene-based weakly basic anion exchange resin in which the ion exchange group is a tertiary amino group).
[0104] [Comparative Example 3] Methanol was purified in the same manner as in Reference Example 1, except that the ion exchange resin was changed to synthetic adsorbent HP20 (manufactured by Mitsubishi Chemical Corporation, a porous styrene-based synthetic adsorbent having no ion exchange groups).
[0105] The evaluation results of the methanol obtained in the Reference Example and Comparative Reference Example are shown in Table 1.
[0106] [Table 1]
[0107] [Example 1] A solution (B) in which tetramethoxysilane and the methanol obtained in Reference Example 1 were mixed at a volume ratio of 4.4:1, and a solution (C) of a 4 mass% aqueous ammonia solution were prepared. A reaction vessel equipped with a thermometer, a stirrer, a supply pipe, and a distillation line was charged with the solution (A) in which the methanol obtained in Reference Example 1, pure water, and ammonia were mixed. The concentration of water in solution (A) was 7.5 mass%, and the concentration of ammonia in solution (A) was 1.2 mass%. While maintaining the temperature of the reaction solution at 31°C, 41 vol% of solution (B) and 11 vol% of solution (C) were added dropwise at a constant rate to 48 vol% of solution (A) over a period of 211 minutes to obtain a dispersion of silica particles. The temperature of the obtained silica particle dispersion was raised to remove methanol and ammonia while adjusting the liquid volume by adding pure water so that the silica particle content was approximately 20 mass%. A silica particle dispersion with a silica particle content of approximately 20 mass% was obtained, and the obtained silica particle dispersion was used as it was as silica sol. The evaluation results of the obtained silica sol are shown in Table 2.
[0108] [Comparative Example 1] The same procedure as in Example 1 was repeated except that methanol in Comparative Reference Example 1 was used for solution (A) and solution (B), to obtain a dispersion of silica particles having a silica particle content of approximately 20 mass %, and the obtained dispersion of silica particles was used as a silica sol as it was. The evaluation results of the obtained silica sol are shown in Table 2.
[0109] [Table 2]
[0110] As can be seen from Table 2, the silica sol obtained in Example 1, which used methanol purified by ion exchange resin, was able to significantly reduce the zinc and iron contents in the silica sol, while the average primary particle size, average secondary particle size, cv value, and association ratio were almost the same as those in Comparative Example 1, which used methanol not purified by ion exchange resin. It is expected that when a silicon wafer is polished using a polishing composition containing the silica sol produced in Example 1, contamination of the silicon wafer surface can be reduced. [Industrial Applicability]
[0111] The silica particles obtained by the method for producing silica particles of the present invention and the silica sol obtained by the method for producing a silica sol of the present invention can be suitably used for polishing purposes, for example, polishing semiconductor materials such as silicon wafers, polishing electronic materials such as hard disk substrates, polishing (chemical mechanical polishing) in the planarization process when producing integrated circuits, polishing synthetic quartz glass substrates used for photomasks and liquid crystals, polishing magnetic disk substrates, and the like, and among these, they can be particularly suitably used for polishing silicon wafers and chemical mechanical polishing.
Claims
1. A method for producing silica particles, comprising the following steps (1) and (2), and not including a step of drying an ion exchange resin: Step (1): Purifying methanol with an ion exchange resin Step (2): A step of adding a solution (B) containing tetraalkoxysilane to a solution (A) containing methanol purified in step (1) to cause a hydrolysis reaction and a condensation reaction of the tetraalkoxysilane.
2. The method for producing silica particles according to claim 1 , wherein the ion exchange resin in step (1) comprises a cation exchange resin and an anion exchange resin.
3. The method for producing silica particles according to claim 2 , wherein the cation exchange resin comprises a strongly acidic cation exchange resin.
4. The method for producing silica particles according to claim 2 or 3, wherein the anion exchange resin comprises a strongly basic anion exchange resin.
5. The method for producing silica particles according to any one of claims 1 to 4, wherein the solution (B) contains methanol purified in the step (1).
6. The method for producing silica particles according to any one of claims 1 to 5, further comprising the following step (3): Step (3): A step of concentrating the dispersion of silica particles obtained in step (2) and replacing the dispersion medium.
7. The method for producing silica particles according to claim 6, further comprising the following step (4): Step (4): A step of subjecting the dispersion of silica particles obtained in step (3) to a pressurized and heated treatment.
8. A method for producing a silica sol, comprising the method for producing silica particles according to any one of claims 1 to 7.
9. The method for producing a silica sol according to claim 8, wherein the content of silica particles in the silica sol is 3% by mass to 50% by mass.
10. The method for producing a silica sol according to claim 8 or 9, wherein the content of zinc in the silica sol is 50 ppb or less.
11. The method for producing a silica sol according to any one of claims 8 to 10, wherein the iron content in the silica sol is 4 ppb or less.
12. A polishing method, comprising polishing with a polishing composition containing silica particles obtained by the method for producing silica particles according to any one of claims 1 to 7.
13. A method for manufacturing a semiconductor wafer, comprising the polishing method according to claim 12.
14. A method for manufacturing a semiconductor device, comprising the polishing method according to claim 12.
Citation Information
Patent Citations
Production of dispersion of low salt silica sol in low boiling point alcohol
JP1998114512A
Polishing particle and polishing material
JP2003133267A
Method for refining non-aqueous liquid material
JP2004181352A
Composition for forming porous film and method for producing the composition, method for producing the porous film, the resultant porous film, interlaminar film and semiconductor device
JP2004269693A
Process for removing trace metal ion
JP2005247770A
